Павло Гнідич і розвиток фольклористичної думки на Сумщині на поч. ХХ ст. - П'ятаченко, С. (Народна творчість та етнографія, 2006)
This article is dedicated to the folkloristic work done by Ukrainian scholar, cultural and social activist and pedagogue Pavlo Hnidych. His folklore recordings consist of five volumes of "Oral Folklore Materials from Poltawska Gubernia, Romenskyi Povit”.